The Impact of Digital Payments on Shopping Culture in the Community of Bengkulu City - Alghaffaru, Muhammad Atha; Benardin, Benardin (East Asian Journal of Multidisciplinary Research, 2024)
This research aims to delve into the impact of digital payment usage on the shopping patterns of the community in Bengkulu City. The research methodology involves comprehensive surveys and meticulous data analysis to identify changes in shopping behavior associated with the adoption of digital payment technology. The results indicate that the significant implementation of digital payments modifies the shopping habits of the community, stimulates efficiency in transactions, and provides a higher level of convenience. The study not only provides an understanding of the shift in shopping practices but also offers a profound insight into the cultural transformation of shopping triggered by financial technological changes